PENGARUH PROFITABILITAS, LEVERAGE DAN UKURAN PERUSAHAAN TERHADAP PENGUNGKAPAN LIMBAH DENGAN KOMITE KEBERLANJUTAN SEBAGAI VARIABEL MODERASI - Yosevin Karnawati; Bambang Sutopo (Paulus Journal of Accounting (PJA), 2025)
The purpose of this study is to analyze the influence of profitability, leverage and company size on waste disclosure with the sustainability committee as a moderating variable. The population is companies in the basic industry, energy and industrial sectors listed on the Indonesia Stock Exchange in 2019-2023, with a total of 296 samples. The data analysis technique uses quantitative analysis and causality, so that multiple linear regression of panel data is used as the analysis tool. The results showed that only profitability and leverage had a positive effect on waste disclosure, while leverage had no effect..The sustainability committee was also unable to strengthen the relationship between profitability, leverage and company size on waste disclosure.